2014
DOI: 10.4028/www.scientific.net/amm.567.62
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Alum Sludge as Phosphate Removal

Abstract: Alum sludge contained a large portion amount of the aluminum derived from the coagulation process in secondary stage water treatment. Alum sludge is discharge to the landfill and it can affect on disposal management. This study investigates the treatment of wastewater using the low-cost adsorption material and also an innovation in green technology for the preservation of the environment. This finding attempts to determine the effectiveness of dewatered water treatment alum sludge as media to remove pollutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Moreover, in Australia, alum and lime sludges produced from groundwater treatment plants are dewatered and then disposed as a waste in landfill site since they contain high level of aluminium and calcium, respectively. Previous studies (Babatunde and Zhao, 2009;Li et al, 2013;Nazirul et al,2014) have shown that alum can effectively remove phosphorus from the wastewater. Similarly, Nair and Ahammed (2015) reported that the 87% of phosphorus removal from the wastewater by using alum sludge.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in Australia, alum and lime sludges produced from groundwater treatment plants are dewatered and then disposed as a waste in landfill site since they contain high level of aluminium and calcium, respectively. Previous studies (Babatunde and Zhao, 2009;Li et al, 2013;Nazirul et al,2014) have shown that alum can effectively remove phosphorus from the wastewater. Similarly, Nair and Ahammed (2015) reported that the 87% of phosphorus removal from the wastewater by using alum sludge.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies using alum sludge for glyphosate removal [9], lead removal [10] and boron removal [11] have also been discovered. However, few studies have been conducted using alum sludge from Malaysian waterworks [12]. Normally, existing form of phosphate easily reacts with metal ions (aluminum) [13].…”
Section: Introductionmentioning
confidence: 99%